The Pollution Profile of Citarik, Cimande, and Cikijing Rivers in Rancaekek District, West Java, Indonesia - Refnilda Fadhilah; Katharina Oginawati; Nur Aisyah Yuniar Romantis (Universitas Trisakti, 2018)
Aim: The objective of this study was to determine the heavy metals pollution profile of Citarik, Cimande, and Cikijing Rivers. Methodology and Result: The method of this research to measured heavy metals was cadmium, chromium, copper and zinc. Determination of sampling point refers to SNI 03-7016-2004. The river water sampling procedure refers to SNI 6989.57-2008 on Water and Wastewater - Section 57. The water sample extraction method refers to Standard Method for the Examination of Water and Wastewater. Sediment sample extraction method refers to EPA Method 200.2-1994. The water sample extraction method refers to Standard Method for the Examination of Water and Wastewater. Sediment sample extraction method refers to EPA Method 200.2-1994. Based on test result and comparison to quality standard of Indonesian Government Regulation No. 82of 2001 on Water Quality Management and Water Pollution Control. The metal concentrations in the sediments were much higher than the concentrations of metals contained in water. This is due to the accumulation of metals in sediments that occur continuously. Conclusion, significance and impact study: The concentrations of four metals in water and sediments after river points higher than before passing the industrial area, it indicates that anthropogenic arising from agricultural activities and textile industry near the rivers of Citarik, Cikijing, and Cimande rivers. The degree of contamination and seasonal variation of heavy metals were high in water and sediment.